A review on the personal protective equipment (PPE) used in occupational radiation protection / Jawidah Adiba Kamarolzeman and Nur Maizatul Azra Mukhtar - Kamarolzeman, Jawidah Adiba; Mukhtar, Nur Maizatul Azra (2020)
The use of personal protective equipment is compulsory as a personal protection and control measure from radiation hazard. The hazard can be a high exposure of primary radiation or could be a low dose of the scattered radiation from the patients' body. Therefore, the workers must wear proper and the best quality of PPE to mitigate the radiation harmful. There are a lot of PPE available in the market with a particular based material, such as lead aprons, latex gloves, thyroid shield, and glasses. All these PPE have their property in terms of design, radiation characteristic, based-materials and others. Therefore, this study is conducted to gather information and findings from the previous study as a systematic review. As a result, 82 articles were retrieved from seven databases and screened out their eligibility. Of these, only 18 articles were eligible and included. Three of them discussed on theoretical such as survey and ten discussed on experimentally study.